Effect of cumulative dexamethasone dose in preterm infants on neurodevelopmental and growth outcomes: a Western Australia experience. Issue 1 (20th July 2020) - Buchiboyina, Ashok Kumar; Yip, Chi Seong Andrew; Kohan, Rolland; Nathan, Elizabeth A; Shrestha, Damber; Davis, Jonathon; Wang, Xiaowei; Sharp, Mary
Abstract : Objective: Comparing the long-term neurodevelopmental and growth outcomes of lower and higher cumulative dexamethasone exposure in preterm infants ventilated for a minimum cumulative duration of 7 days. Design: A retrospective cohort medical chart review of infants born in Western Australia <29 weeks' gestation between January 2007 and May 2016 who were mechanically ventilated >7 days. Intervention: No dexamethasone (controls) or a total cumulative dexamethasone dose of <2 mg/kg (lower) and ≥2 mg/kg (higher). Main outcome measures: Long-term disability at 2 and 5 years and growth measurement outcomes at 2 years of age. Results: Dexamethasone was given to 104 infants (66 with cumulative dose <2 mg/kg; 38 with cumulative dose ≥2 mg/kg), and 324 infants were controls. There was no difference in odds of long-term disability in infants with any dexamethasone exposure compared with controls (aOR: 0.90, 95% CI 0.34 to 2.02, p=0.784). No difference in long-term disability was found between the lower and higher groups (p=0.494). The prevalence of cerebral palsy (Gross Motor Functional Classification System level ≥2) between the control, lower and high-dose groups did not differ significantly (5.8% vs 4.0% vs 0%). The higher dose group had lower mean weight z-score (mean effect: −0.83, 95% CI: −1.54 to −0.01, p=0.023), height z-score (mean effect: −0.63, 95% CI: −12.5 to −0.01, p=0.048) and head circumference z-score (mean effect: −0.65, 95% CI: −1.25 to −0.05, p=0.035) compared with controls. Conclusions: In our cohort, dexamethasone use was not associated with increased odds of long-term disability. Dexamethasone use was associated with lower growth measurements compared with controls.